Study of Shakespeare Thoughts of Women in the Movie Titus: Exploring the Concept of Revenge in Shakespeare's Titus Andronicus (Journal of Advances and Scholarly Researches in Allied Education, 2016)
In most of the plays written by William Shakespeare, Some act of revenge is still there, no exception is Titus Andronicus (1593-1594). As Titus Andronicus' main subject is revenge, in the study tries to discuss this issue. The thesis discusses the concept of revenge and its characteristics, and the influence of Seneca on Elizabethan revenge authors generally, in particular William Shakespeare, influence of The Spanish Tragedy by Thomas Kyd Jew of Malta's Christopher Marlowe.